Advanced in-situ control for III-nitride RF power device epitaxy. (26th March 2018) - Brunner, F; Zettler, J-T; Weyers, M
Abstract: In this contribution, the latest improvements regarding wafer temperature measurement on 4H-SiC substrates and, based on this, of film thickness and composition control of GaN and AlGaN layers in power electronic device structures are presented. Simultaneous pyrometry at different wavelengths (950 nm and 405 nm) reveal the advantages and limits of the different temperature measurement approaches. Near-UV pyrometry gives a very stable wafer temperature signal without oscillations during GaN growth since the semi-insulating 4H-SiC substrate material becomes opaque at temperatures above 550 °C at the wavelength of 405 nm. A flat wafer temperature profile across the 100 mm substrate diameter is demonstrated despite a convex wafer shape at AlGaN growth conditions. Based on the precise assignment of wafer temperature during MOVPE we were able to improve the accuracy of the high-temperature n-k database for the materials involved. Consequently, the measurement accuracy of all film thicknesses grown under fixed temperature conditions improved. Comparison of in situ and ex situ determined layer thicknessess indicate an unintended etching of the topmost layer during cool-down. The details and limitations of real-time composition analysis for lower Al-content AlGaN barrier layers during transistor device epitaxy are shown.